PENGARUH BUDAYA MEMBACA DAN DISIPLIN BELAJAR MELALUI MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR - Yika Dorti Simanjuntak; Teddy Rusman; Nurdin Nurdin (FKIP Unila, 2013)
This study aims to determine whether there is an influence of reading and learning through motivation berpreastasi discipline on learning outcomes Integrated Social Science. Testing the hypothesis in this study is the use of path analysis. Based on the analysis of the obtained results as follows. 1. There are cultural influences on reading achievement motivation 2. There is a discipline studying the influence of achievement motivation 3. There is a reading of cultural influences on learning outcomes 4. There is a discipline studying the effect on learning outcomes 5. There influence student achievement motivation on learning outcomes 6. There is a reading of cultural influences on learning outcomes through achievement motivation 7. There is a discipline studying the effect on learning outcomes through achievement motivation 8. There are cultural influences on reading and learning discipline and achievement motivation 9. There are cultural influences through the discipline of learning to read and achievement motivation on learning outcomes.Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh budaya membaca dan disiplin belajar melalui motivasi berpreastasi terhadap hasil belajar IPS Terpadu. Pengujian hipotesis dalam penelitian ini adalah menggunakan analisis jalur. Berdasarkan analisis diperoleh hasil sebagai berikut. 1. Ada pengaruh budaya membaca terhadap motivasi berprestasi 2. Ada pengaruh disiplin belajar terhadap motivasi berprestasi 3. Ada pengaruh budaya membaca terhadap hasil belajar 4. Ada pengaruh disiplin belajar terhadap hasil belajar 5. Ada pengaruh motivasi berprestasi siswa terhadap hasil belajar 6. Ada pengaruh budaya membaca terhadap hasil belajar melalui motivasi berprestasi 7. Ada pengaruh disiplin belajar terhadap hasil belajar melalui motivasi berprestasi 8. Ada pengaruh budaya membaca dan disiplin belajar terhadap motivasi berprestasi 9. Ada pengaruh budaya membaca dan disiplin belajar melalui motivasi berprestasi terhadap hasil belajarKata kunci : membaca, disiplin, motivasi, hasil belajar